Incubation period of COVID-19: analysis of COVID-19 cases admitted in a tertiary care center, northern district of Kerala, India - Saraswathy, Anitha Subhadra; Sanya, Rameela; Kumaran, Jayasree Anandabhavan (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus disease 19 (COVID-19) started as pneumonia of unknown cause detected first in Wuhan, China in December 2019 and spread as a pandemic affecting more than 200 countries worldwide. The most common symptoms of COVID-19 are fever, dry cough, breathing difficulty and tiredness. The median incubation period is about 5 days as per current understanding. The present study was done to estimate the median incubation period of COVID-19 cases admitted in a tertiary care center in north Kerala. Methods: This cross-sectional study included COVID-19 cases admitted in a tertiary care center during three months study period. Results: The median incubation period of COVID-19 was estimated to be 4 days (interquartile range 7). It was also found that females, those persons with comorbidities and those who got infected by local transmission had a longer mean incubation period compared to males, those without comorbidities and imported cases, respectively. Conclusions: The median incubation period of COVID 19 was estimated to be 4 days. Factors like presence of comorbidities, gender, type of transmission were found to affect incubation period, but further studies are needed to have a thorough understanding.